أفق قراءة جديدة لرواية أولاد حارتنا لنجيب محفوظ - العلمي, مسعودي (University of Eloued جامعة الوادي, 2012)
لقد اقتضى فهم النص " أولاد حارتنا" من زاوية الأفق الراهن، العودة إلى تاريخ تلقيه قصد الإحاطة بالآفاق التاريخية التي أجيب فيها عن أسئلة القراء الأوائل والقراء اللاحقين. الآن وقد انتهينا من إعادة كتابة هذا التاريخ ،سننتقل إلى مساءلة ذلك النص في ضوء أفق جديد نسبيا . ولن تكون قراءتنا نموذجا بديلا ووحيدا وإنما سنقوم بانتقاء أحد التحققات الممكنة للقارئ الضمني أو النموذجي في رواية أولاد حارتنا Understanding the text of the "the children of our neighborhood" from the perspective of the current horizon required a return to the date of its receipt in order to capture the historical horizons in which the questions of the first readers and the subsequent readers were answered. Now that we have rewritten this date, we will move to the accountability of that text in the light of a relatively new horizon. Our reading will not be an alternative and a single model, but we will select one of the possible probes of the implicit or typical reader in the novel "The children of our neighborhood"
Keywords: الرواية، نجيب محفوظ، رواية اولاد حارتنا; The novel, Naguib Mahfoud, the novel of the children of our neighborhood